One‐Dimensional Phosphorus Nanostructures: from Nanorings to Nanohelices. Issue 63 (19th October 2017) - Sansone, Giuseppe; Maschio, Lorenzo; Karttunen, Antti J.
Abstract: Phosphorus nanorings and nanohelices—speculated to exist over 20 years ago—have been systematically derived from one parent structure and studied with quantum chemical methods. The (P8 P2 ) n nanorings have been recently synthetized inside carbon nanotube templates, and our comprehensive analysis of possible structural arrangements strongly supports the possibility to experimentally determine the closely related (P8 P2 ) n nanohelices. The nanohelices possess very low stiffness, suggesting interesting mechanical properties with nano‐spring‐like behavior. Abstract : Phosphorus nanohelices : We present a family tree of curved red phosphorus modifications and introduce novel phosphorus nanohelices with exciting mechanical properties.